Primary malignant melanoma of the middle ear mucosa: a case report - (:unkn) unknown (My University, 2006)
Primary involvement of the middle ear and mastoid mucosa by malignant melanoma (MM) has been rarely reported. We report an 81-year-old Caucasian woman presenting with otalgia, left-sided aural fullness, and hearing loss. Otoscopic examination revealed a purple-colored polyp that appeared to be vascular, occupy left external auditory canal (EAC). The computed tomography scanning showed a mass in soft tissue density, filling the tympanic and mastoid cavities, eroding the mastoid cortex, and invading medial and central parts of the EAC. A biopsy was performed with the diagnosis of MM. The patient underwent subtotal temporal bone resection with radical neck dissection. Dacarbazine was given postoperatively. The case presented herein emphasizes the need to be aware that MMs can arise in the middle ear and mastoid cavity. An index of suspicion in the differential diagnosis of temporal bone tumors is necessary for early recognition.
Keywords: Female; Humans; Aged; Aged, 80 and over; Tomography, X-Ray Computed; Combined Modality Therapy; Diagnosis, Differential; Fatal Outcome; Ear Neoplasms; Melanoma; Ear, Middle